Management of Asta-Ja System - Poudel, Durga (Journal of Comparative International Management)

(untitled) (Management Futures, 2016)
About a decade ago, I founded the Asta-Ja Framework which identifies Eight Ja—the Nepali letter “Ja,”—meaning Jal (water), Jamin (land), Jungle (forest), Jadibuti (medicinal and aromatic plants), Janashakti (manpower), Janawar (animlas), Jarajuri (crop plants), and Jalabayu (climate), and proposes their sustainable conservation, development, and utilization for fast-paced socio-economic transformation of Nepal. It is a scientific, holistic, systematic, self-reliance, and multidisciplinary grassroots-based framework for conservation, development and utilization of Asta-Ja resources. For its practical application, I proposed eight principles: 1) community awareness, 2) policy decision making, 3) community capacity-building, 4) interrelationships and linkages, 5) comprehensive assessment, 6) sustainable technologies and practices, 7) institutions, trade and governance, and 8) sustainable community development and socio-economic transformation. The first decade of its implementation in Nepal characterized with a vigorous community outreach, strong membership drive, sound policy advocacy, heavy engagement of high-level government officials and dignitaries, community capacity-building, disaster relief works, and cutting-edge research and development. Future direction for its effective implementation include: 1) institutional strengthening, 2) coordination with governmental agencies and other stakeholders in planning and management of Asta-Ja resources, 3) expedited research and development on Asta-Ja resources, 5) formation of Asta-Ja Consortium, 6) development of a comprehensive Asta-Ja Data Portal, and 7) the establishment of Asta-Ja Think Tank.